1995
DOI: 10.1103/physrevb.52.10188
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Jahn-Teller splitting ofC60inC60

Abstract: Pulsed EPR measurements of the transverse and longitudinal relaxation times of the C« -anion radical in crystalline C«-tetraphenylphosphoniumchloride were done at temperatures from 4 to 40 K. Above 40 K to room temperature the longitudinal relaxation time was taken from the cw-EPR linewidth. The low-temperature data are explained in terms of local magnetic fluctuations, slow C«motion, and localized two-level states related with the local disorder. The relaxation data at higher temperatures reveal experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Rather, low-lying states contribute to the line width of the broad signal via Orbach relaxation. 350 In 1995, Huang and co-workers made a related proposal that C 60 -could exist in two different ground states depending on ion-pairing effects. 322 They observed that the relative intensity of the sharp versus broad signal in KC 60 ‚THF increased as the solvent was removed under vacuum.…”
Section: Problem Of the Sharp Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, low-lying states contribute to the line width of the broad signal via Orbach relaxation. 350 In 1995, Huang and co-workers made a related proposal that C 60 -could exist in two different ground states depending on ion-pairing effects. 322 They observed that the relative intensity of the sharp versus broad signal in KC 60 ‚THF increased as the solvent was removed under vacuum.…”
Section: Problem Of the Sharp Signalsmentioning
confidence: 99%
“…346 A more quantitative understanding of the broad, temperature-dependent signal is coming from pulsed EPR measurements of the traverse and longitudinal relaxation times of C 60 -in a tetraphenylphosphonium salt. 350 Its origin clearly lies in the dynamic nature of the small Jahn-Teller distortion associated with degeneracy of the (t 1u ) 1 ground state. This gives rise to a 2 A ground state and a close lying 2 E excited state 179 which can give rise to signal broadening by an Orbach relaxation process.…”
Section: Temperature Dependence Of the Line Width (∆H Pp )mentioning
confidence: 99%
“…Thus, we supplement the vibrational studies reported to date 8,9,12,16 and complement the previous EPR temperature dependence work. 6,11,31 …”
Section: Introductionmentioning
confidence: 99%
“…6,11,30 Pulsed EPR measurements on the chloride-containing salt show Orbachtype spin-lattice relaxations, consistent with JT vibronic excitations. 31 ͑Ph 4 P͒ 2 IC 60 can be compared to other solid-state fullerene materials with regards to the charge and symmetry states of the ball and the degree of separation between balls. The A n C 60 alkali-metal doped fullerides contain the negatively charged C 60 ball (chargeϭn) which is subject to a JTE for 1рnр5.…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared-visible spectroscopic experiments on (Ph 4 P) 2 IC 60 show that the electronic and vibrational properties of the C À 60 anion are hardly perturbed by the counterion environment [6]. Detailed temperaturedependent studies of (Ph 4 P) 2 IC 60 have been carried out by electron paramagnetic resonance (EPR) [4,7,8], Raman scattering [9], and infrared spectroscopy [10,11], which demonstrate the dynamic JT effect at room temperature. During cooling down (Ph 4 P) 2 IC 60 undergoes a transition to a static JT distorted state in the temperature range 120-140 K.…”
mentioning
confidence: 99%